Sergey Esenin: the Baku Period of Life and Creativity of the Great Russian Poet (ENTHYMEMA, 2018)
Sergey Esenin is one of the most read Russian poets and at the same time remains one of the least studied. Thus, this article is devoted to the Baku period of Esenin's life, as he lived in Azerbaijan in 1924-1925. We have studied this period on the basis of newspaper articles, contemporaries’ memoirs, as well as scientific works of 60 Azerbaijani researchers. These works are important not only for the popularization of Esenin's poetry and classical Russian poetry in general, but also for Azerbaijani-Russian literary and cultural ties.